Implementation of the Money Laundering Law as a Predicate Crime during the Covid-19 Outbreak - Bernieka Nur Annisa; Cony Dehas Ratna Devi; Sholahuddin Al-Fatih; Mohammad Affan (Fakultas Hukum Universitas Hang Tuah, 2022)
Cases of criminal acts of corruption and Money Laundering have such fundamental ties. In this case the act of corruption is a part of the special criminal law in addition to having special specifications or different from the general criminal law or other, such as a deviation of procedural law and when viewed from the material regulated, the act of corruption directly or indirectly there is a the case or further criminal action from the existence of this criminal act of corruption resulting in a loss that affects the country's economy, namely by committing the crime of money laundering as an act of laundering or busting the trace rather than the original criminal activity. In addition, in these two acts there is a form of indictment which is very important in the Money Laundering Act because this is very much a part of the determination by the judge in proving an element of guilt from the offender, therefore, the preparation of an appropriate indictment in the Criminal Act of Laundering The money in which the part can't be ignored. So, in the development of the case, we need to know a lot about the continuity of corruption in the money laundering law, the use of money laundering legislation in its handling of corruption to optimize the efforts to recover state losses, and also the mechanism of imposing criminal penalties in proving the crime of money laundering without first proving the crime predicate as the most important element in imposing sanction.